Developing children and youth reading culture for national development: the role of library services and access to education (2017)
The decline in reading culture of Nigerian children and youth has become a subject of discussion in recent times. The conclusion reached at different debates and meetings organised to deliberate on the way out has emphasized the need to improve the reading culture of children and youth to enable them contribute to national development. This paper therefore examined the significant role the Provision of library Services could play in developing reading culture and highlighted some strategies that librarians and other stakeholders could adopt. The paper also X - rayed the poor state of education in Nigeria and the inability of a high percentage of Nigerian children to access quality education. The paper concludes by making recommendations that can enhance the acquisition of reading culture by Nigerian children and youth.